A Narrative Review of Weight-bearing Computed Tomography Scans: How have They Influenced the Management of Common Foot and Ankle Pathologies? - Brittany M Ammerman; Amanda I Zeng; Rachel M Thompson; Scott J Ellis (Journal of Foot and Ankle Surgery (Asia Pacific))
Weight-bearing computed tomography (WBCT) has significantly advanced the management of foot and ankle pathologies by offering more accurate and comprehensive imaging compared to traditional radiographs and non-WBCT scans. This narrative review seeks to assess how WBCT has influenced the diagnosis, treatment, and postoperative assessment of common foot and ankle conditions, including hallux valgus, progressive collapsing foot deformity (PCFD), syndesmotic instability, and ankle arthritis. By capturing three-dimensional (3D) load-bearing images, WBCT enables more accurate assessments of bone and joint alignments as well as the severity of deformity. In doing so, WBCT enhances the diagnostic process, precision of surgical planning, and assessment of patient outcomes. While WBCT has already provided more insight into foot and ankle biomechanics, further research must be conducted to assess its use in other foot and ankle deformities as well as its potential to redefine foot and ankle pathologies, including their classification systems.